1984
DOI: 10.1002/ajpa.1330640103
|View full text |Cite
|
Sign up to set email alerts
|

Secular change in growth of native children and adolescents at high altitude Huancayo, Peru (3,280 meters)

Abstract: Stature and weight of native children, adolescents, and adults at Huancayo , Peru (3,280 meters), were measured in 1977, 1978, and 1982 and compared with mean statures and weights reported in previous studies. The data indicate that in Huancayo there has been a secular increment in child stature, sitting height, and weight from 1937 to 1978-1982. The observed changes in stature are related to a proportionally greater increment in leg length relative to trunk length. It is concluded that the observed secular in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Such observations were also reported for Amerindians living at high altitude in the Andes (Gonzales et al, 1982(Gonzales et al, , 1984. Thus it would have been interesting to compare the amount of increase for leg length and sitting height, or the sitting height/stature ratio of the 1972 The present study showed sex differences in secular gains such that males experienced greater increase in stature than females between 1972 and 1987.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Such observations were also reported for Amerindians living at high altitude in the Andes (Gonzales et al, 1982(Gonzales et al, , 1984. Thus it would have been interesting to compare the amount of increase for leg length and sitting height, or the sitting height/stature ratio of the 1972 The present study showed sex differences in secular gains such that males experienced greater increase in stature than females between 1972 and 1987.…”
Section: Discussionsupporting
confidence: 70%
“…did not find a secular increase in adult body size, they attributed their findings to an earlier sexual maturation in the 1980 group. In a further study on Huancayo natives 6-26 years (3,280 m, Peru), the same authors found a significant secular increase for stature and weight from 1937 to 1978/82 in children and adults (Gonzales et al, 1984). The authors interpreted the secular increase as a consequence of improved living conditions and a greater amount of nonnative genes in the 1978/82 sample.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Nevertheless, effects of secular change on these results cannot be excluded, as the studies on the comparative samples were published between 1944 and 1994, over a period of fifty years. It has been shown that most of the secular increase in stature in Amerindians (Gonzales et al, 1984) and other populations (e.g., Tanner et al, 1982) can be attributed to increase in leg length. Low et al (1981) reported that in Chinese girls, the observed secular increase in standing height "is the result of the secular gain inboth sitting height and lower limb length" (p .86).…”
Section: Discussionmentioning
confidence: 99%